Prevalence of Isopora suis Coccidiosis and factors associated with infection in pig herds in Batangas Province, Philippines - Padilla, M. A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
Fecal samples were collected from four hundred sixty two 5- to-30-d-old litters in 32 commercial swine farms in Batangas Province over a period of 9 months from June 2001 to March 2002. Owners and managers of these farms were interviewed to obtain data on 12 putative variables that may influence the development of I. suis coccidiosis. I. suis oocysts were detected in 30.6% litters in 27 out of the 32 (84.4%) farms surveyed. I. suis fecal oocyst counts ranged from 0 to 306,627 OPG (mean OPG 3235). Diarrhea was recorded in 61 (62.88%) of L suis-positive litters and in 247 (67.67%) of l. suis-negative litters, suggesting that other enteropathogens may play a role in diarrhea. None of the factors examined were significantly associated with the development of I. suis coccidiosis.